Pola Bermain Anak Usia Dini di Era Gadget Siswa Paud Mutiara Bunda Sukodono Sidoarjo - Sucipto, Sucipto; Huda, Nuril; Huda, Nuril (Jurnal Ilmiah FONEMA : Jurnal Edukasi Bahasa dan Sastra Indonesia, 2016)
Ativities Children’s playground has develop over time, which is reflected in the pattern of paly and type of play equipment used. One form of technology that is very popular these days is the gadget. The use of these can be found everywhere, both in adults to children in early age including children in Mutiara Bunda Palgroup, SUkodono Sidoarjo. It raises question to do research including: (1) How do the patterns of early chilboad play in the era of Gadged? (2) how far early chilboad have been using gadgeds? (3) what positive and negative impact of the use of gadgets? While empirical studies done by canducting research on 36 children in in Mutiara Bunda Palgroup, SUkodono Sidoarjo. Data obtained from the parents by using questionaires and the data has been analysed. The finding of the studi states that 50% of the 36 children chose to play a pssive form and 44% of active and passive play. The use of gadgets have positive and negative effect for children ins early chilbood